Unveiling the coverage patterns of newspapers on the personal data protection act - Chua, Hui Na *; Wong, Siew Fan *; Chang, Younghoon; Libaque-Saenz, Christian Fernando (Elsevier, 2017)
collected, used, processed and even transferred to third party organizations. To protect the privacy of data owners and the security of these data, the Malaysian government has enforced the Personal Data Protection Act (PDPA) in 2013. Several studies found that Malaysians have low awareness of the PDPA. Prior literature also shows that the framing of news stories by the media has significant influence on public awareness and perception toward a covered topic. In this paper, we investigated how the Malaysian newspapers frame the PDPA news. We extracted a total of 793 news articles between January 1st 2010 and July 31st 2015 from ten local English newspapers. The results show that newspapers in general have not given the PDPA enough attention considering its potential impact on data privacy and security. Nonetheless, newspapers do publish significantly higher number of PDPA articles after the enforcement period compared to before the enforcement period. The newspapers also mostly position the PDPA news in the Technology section. The results also show that more PDPA news originated from foreign sources compared to local sources or the government. Our findings provide insights into the coverage patterns of local newspapers and the insufficient level of prominence given to the PDPA. The findings have implications for both the government and the newspapers as a media.